ANALISIS PENERAPAN AKUNTANSI SYARIAH SISTEM BAGI HASIL DALAM PROGRAM TABUNGAN BANK SYARIAH MANDIRI CABANG MEDAN - Atika Atika (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
This study aims to determine how the calculation of the profit sharing system mudharabah savings program in an independent Islamic bank and whether the application of Islamic accounting in the profit sharing system mudharabah savings program in an independent Islamic bank is in accordance with the principles of Islamic accounting (PSAK 105). The approach used in this research is descriptive approach. The results showed that Bank Syariah Mandiri Cabang Medan uses the profit sharing method in the profit sharing principle of mudharabah financing, where operating income is reduced by operating expenses to obtain the operating income. Penalties imposed on customers are recognized by Bank Syariah Mandiri Cabang Medan as non-operational income and is used for social funds. Revenue sharing is seen as meeting the definition of income. The reason is that revenue-sharing income is income that gives the addition of assets in the form of cash which is the inflow that comes from profit sharing mudharabah financing can increase the profit / profit of Bank Syariah Mandiri Cabang Medan. The accounting treatment of revenue (profit sharing) mudharabah financing implemented by Bank Syariah Mandiri Cabang Medan, in accordance with PSAK No. 105 concerning Mudharabah Accounting.